Desery i wypieki domowe : dawne i nowe - Zawistowska, Zofia (Warszawa : Instytut Wydawniczy Zwiazkow Zawodowych ; BiaLystok : Wydawnictwo Bialowieza, 1991)
Recipes for home-made desserts and pastries.
Includes index.
Keywords: Desserts; Pastry; Baking